Problematizing the methodology: challenges, conflicts, and contradictions in the study of queer-feminist zines in the Iberian Peninsula - López Casado, Laura (2022)
My research project studies feminist and queer zines inside academia during the last decades of the Twentieth Century and the beginning of Twenty-first Century in Spain and Portugal. When I started the research some of the conflicts and contradictions were immediately revealed. The necessity of definition of my study object, the process of recollecting zines, the legitimacy of building-up an investigation like this inside the academia... all of these raise controversial questions that the research needs to address. Thus, it was imperative to think about the approach and how to address the methodology. One of the most urgent is to reflect on the process of institutionalization of counter-hegemonic knowledges, with all the inherent dangers, including the deactivating of political strategies that are specific to movements.